Women's Work-Life Balance in Hospitality: Examining Its Impact on Organizational Commitment - Liu, Ting; Gao, Jie; Zhu, Mingfang; Jin, Shenglang (Frontiers in Psychology, 2021)
Women account for a large proportion in the hotel industry. Work-life conflict has become one of the main obstacles to the organizational commitment of women. Thus, this study investigates the relationship between work-life balance, as an independent variable, and organizational commitment, as a dependent variable, for women. Specifically, we examine women’s work-life balance in the hospitality industry, comparing women’s organizational commitment under different levels of work-life balance. Then, we assess whether women's work-life balance and organizational commitment are associated with their sociodemographic characteristics (i.e., age, education, working years, and position level). Data were collected from 525 women employees in China. Multiple linear regression analyses were conducted to identify the relationship between work-life balance and organizational commitment. The results showed that work-life balance had a significant effect on organizational commitment. There was also a significant relationship between women’s sociodemographic characteristics, work-life balance and organizational commitment.